Evaluation of the Plant Essential Oils to Control of Dry Bubble Disease (Lecanicillium fungicola (Preuss) Zare) in the White Button Mushroom - Allahyari, Mahmmod; Gholamnezhad, Jalal; Maleki, Mojdeh (Polish Journal of Natural Sciences, 2023)
Edible mushrooms are not only a rich source of nutrients and proteins, but also some of the species produce medicinal compounds. The white button mushroom (Agaricus bisporus Imbach) was first cultivated in France. Dry bubble disease with Lecanicillium fungicola (Preuss) Zare and Gams is one of the most important diseases that cause damage to edible fungi. One of the easiest ways to control edible fungal diseases, especially dry blisters, is to use chemical fungicides such as carbendazim. Given that a small number of fungicides are currently available to control edible fungal diseases. However, the total resistance of fungal pathogen to chemical fungicides is due to their frequent use, so the use of plant essential oils can be an alternative method for controlling fungal diseases. In this study, the effect of plant essential oils including fennel, ferula, harmel, thymus and satureja was studied by two methods as the plant essential oils mixing with the culture medium and using the paper disk on the pathogen caused the bubble disease and edible mushroom. In another section of this research, it was investigated the effect of plant essential oils, including thyme and satureja, on the fungal pathogen in the salon and on edible fungi. The results of the mixing essential oils assay with the culture medium showed that the essential oil of thyme and ferula at a concentration of 1000 ppm inhibited the growth of the pathogen at 90.42% and 78.44%, respectively. These plant essential oils showed the highest inhibition of the growth of edible fungi. The results of the paper disk test showed that all the essential oils used in this study were able to reduce the growth rate of the pathogen. 1000 ppm concentration had the highest inhibition of the pathogen growth among all of the concentrations, and thyme essential oil with 85.41% showed the highest inhibition pathogen growth, followed by fennel, ferula and satureja essential oils with values of 74.78, 73.72 and 70.22%, respectively. The results of the study in the salon (in vivo), showed that the essential oils of thyme and fennel increased the number of healthy fungi by 77.19 and 55.63%, respectively, compared to the control. According to the results of the in-vitro and in-vivo (salon) of the essential oils of thyme, fennel and ferula showed a high capacity to control edible fungal diseases, especially bubbles.